Trade with a Produced Transportation Good - John M. Hartwick (Queen's University, Department of Economics, 1971)
This paper is in one sense the analysis of a particular case of the Hadley and Kemp model (described in the paper). We shall focus on two region or country trade with two orthodox commodities plus a produced transport commodity. We will observe that balance of payments disequilibrium is a general result with trade with endogenous transport costs and finally that reductions in transport costs may not result in factor prices moving closer together.
Keywords: 330